SEASONAL FLUCTUATION OF LACE BUG Stephanitis pyri (F) (HEMIPTERA: TINGIDAE) IN ERBIL-IRAQ - MUHAMMED, SARKAUT HUSSEIN (Journal of Duhok University, 2021)
This investigation conducted during the two successive seasons 2012-2013 in orchards within Erbil city to follow seasonal fluctuation of Stephanitis pyri. S. pyri start appear in the first week of April and reached a peak level 13.90, 11.4 in third week of August for the two years respectively when the mean temperature was ranged 33-34°C and R.H. 24-29%. Correlation values for lace bug incidence with weather parameters showed that maximum and minimum RH had negative influence on lace bug population. The change in the level of infestation was due to difference in environmental temperature, relative humidity. Field investigation pointed out that the female’s activity of S. pyri began during the period from 1st week of April onward 4th week of October through which it laid their eggs